2003
DOI: 10.1074/jbc.m300847200
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Involvement of p38α MAPK in the Production of Anti- and Proinflammatory Cytokines Using an SB 203580-resistant Form of the Kinase

Abstract: Despite its lack of specificity, the inhibitor SB 203580 has been widely used to implicate p38 mitogen-activated protein kinase (MAPK) in the synthesis of many cytokines. Here we show unequivocally that the production of interleukin (IL)-1␤, IL-6, IL-10, and tumor necrosis factor ␣ (TNF␣) requires p38 MAPK activity by demonstrating that the inhibitory effects of SB 203580 were reversed by expression of an SB 203580-resistant form of p38␣ (SBR-p38␣) that fails to bind to SB 203580. This strategy established the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 42 publications
2
44
1
Order By: Relevance
“…Activation of p38 MAPK occurs in response to ischemia in many organs and promotes cellular stress responses such as proliferation, differentiation and production of proinflammatory cytokines (66,67). IRI of the kidney results in the activation of p38 MAPK, whereas inhibition of the activity of this p38 MAPK in renal IRI attenuates dysfunction and injury (68).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…Activation of p38 MAPK occurs in response to ischemia in many organs and promotes cellular stress responses such as proliferation, differentiation and production of proinflammatory cytokines (66,67). IRI of the kidney results in the activation of p38 MAPK, whereas inhibition of the activity of this p38 MAPK in renal IRI attenuates dysfunction and injury (68).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…Several recent studies have reported that suppression of MAPKs in mast cells may be a useful tool to reduce mast cell number in the inflammatory response (Koranteng et al, 2004). It was reported that p38 MAPK inhibitor suppressed IL-6 and TNF-␣ production in monocytic or mast cells (Guo et al, 2003;Jeong et al, 2003), and inhibition of p38 MAPK and ERK also attenuated COX activity (Borsch-Haubold et al, 1998). In addition, P38, ERK, and JNK are known to participate in the pathway of iNOS expression (Wang et al, 2004).…”
Section: Sc-236 Suppresses Phosphorylation Of Mapks In Hmc-1 31mentioning
confidence: 99%
“…Inhibition of eNOS activity also attenuates the cardioprotective effects of EPO (44). Recently, Su et al (45) have demonstrated that CD131, when activated by EPO, is able to activate Akt Activation of p38 MAPK promotes cellular stress responses such as proliferation, differentiation and production of proinflammatory cytokines and occurs in response to ischemia and hemorrhage in a number of organs (46,47). HR results in the activation of p38 MAPK (in male animals), while inhibition of the activity of this p38 MAPK in hemorrhagic shock attenuates renal, cardiac and lung injury (48)(49)(50).…”
Section: P a T E L E T A L | M O L M E D 1 7 ( 9 -1 0 ) 3 -9 2 mentioning
confidence: 99%